Responsive early childhood parenting, preschool enrollment, and eventual student learning outcomes: a cross-country analysis using hierarchical linear modeling with TIMSS 2019 data - Bhutoria, Aditi; Aljabri, Nayyaf; Bose, Saheli (International journal of child care and education policy (Seoul), 2025)
This paper examines whether parental engagement in early childhood and preschooling act as substitutes, or whether their joint effect enhances students’ learning outcomes. We utilize the TIMSS 2019 dataset and employ a hierarchical linear modeling (HLM) approach to analyze data from 52 countries, ensuring a robust examination of cross-national variations. Although extant literature proposes that parental engagement and preschooling are likely to function as substitutes, our analysis reveals that they can also serve as complements. For instance, a one-unit increase in the TIMSS ECEC parental engagement index is associated with an estimated increase of 0.58 and 0.85 units in math test scores for students with up to one and two years of preschooling, respectively. In the case of science, for students with three or more years of preschooling, our findings suggest a substitutive relationship between parental engagement and preschool participation. In addition, we find that home literacy and numeracy activities undertaken by parents influence both math and science scores, albeit differently. Furthermore, we observe that a higher degree of parental engagement, combined with preschooling, yields the largest test score gains in countries with a greater proportion of children already enrolled in preschool, thereby making a case for expanding preschool access.